Financial Literacy and Dimensions: A Systematic Roadmap for Future - Chand Kiran, Khujan Singh (European Economic Letters (EEL), 2024)
This review paper presents an understanding of basic concepts of financial literacy and its dimensions. This paper is based on secondary data which were collected from previous research papers and past data. The purpose of this paper is to analyze the level of financial literacy around the world by reviewing the existing literature. Main focus of the study is to know about the different dimensions of the financial literacy and to study interrelationship among financial knowledge, financial attitude, financial behavior and financial self-efficacy. Further, a model of financial literacy is also formed with the help of reviewed literature which can be used for future research. Another objective was to know about the research gaps in the existing literature and to find out any other dimensions or variable under financial literacy. This reviewed literature depicts that level of financial literacy around the world is very low and most of the available reviewed literature studied teachers, students, households and stock market participants but other sections of the society hardly targeted.